1980
DOI: 10.1056/nejm198011273032203
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemia and Glucose Intolerance: Evidence for Tissue Insensitivity to Insulin

Abstract: Although hypophosphatemia is commonly present in diabetics, little is known about its isolated effects on glucose and insulin metabolism. We therefore investigated glucose metabolism in six nondiabetic subjects with chronic hypophosphatemia. When glucose was infused to maintain a constant hyperglycemic level (125 mg per deciliter [6.9 mmol per liter] above basal levels), the glucose infusion rate was 36 per cent less in the hypophosphatemic group than in controls (4.90 +/- 0.34 mg per kilogram of body weight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 15 publications
9
93
0
Order By: Relevance
“…There was a significant association of low serum phosphate concentrations with high 2-h blood glucose levels independent of anthropometric parameters like percent body fat, age and gender. These findings are in line with several other studies which demonstrated a significant correlation between serum phosphate, glucose tolerance (DeFronzo and Lang, 1980;Campillo et al, 1982) and adiposity (Lindgarde and Trell, 1977;Haglin et al, 2001). Especially the inverse correlation between BMI and low serum phosphate concentrations has been described earlier (Lind et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There was a significant association of low serum phosphate concentrations with high 2-h blood glucose levels independent of anthropometric parameters like percent body fat, age and gender. These findings are in line with several other studies which demonstrated a significant correlation between serum phosphate, glucose tolerance (DeFronzo and Lang, 1980;Campillo et al, 1982) and adiposity (Lindgarde and Trell, 1977;Haglin et al, 2001). Especially the inverse correlation between BMI and low serum phosphate concentrations has been described earlier (Lind et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…This finding could be confirmed in a smaller group of subjects using the gold standard for measurement of IS, the hyperinsulinemic euglycemic clamp. Moreover, these results are in line with findings in patients with hypophospatemia caused by pHPT (DeFronzo and Lang, 1980;Sowers and Draznin, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…that the observed association is confounded by other causal factors related to the serum levels of calcium and insulin sensitivity, such as BMI, physical activity, intake of coffee or alcohol, or excess of oral intake of calcium. Hypophos-phataemia and hypercalcaemia are in part associated, and in some previous studies low serum levels of phosphate have also been related to decreased insulin sensitivity [35]. However, our results remained robust even after adjustment for serum phosphate concentration (model C).…”
Section: Possible Mechanisms For Observed Associationssupporting
confidence: 45%
“…39,40 In peripheral tissue this increase in intracellular calcium inhibits insulin stimulated glucose uptake and causes insulin resistance. 41,42 There is evidence that hypophosphatemia decreases insulin sensitivity 43 and that phosphate supplementation improves glucose tolerance. Phosphate is involved in the energy balance and ATP generation.…”
Section: Discussionmentioning
confidence: 99%